Safety and effectiveness of a new ophthalmic viscosurgical device: randomized, controlled study. Issue 9 (8th September 2022) - Packer, Mark; Berdahl, John P.; Goldberg, Damien F.; Hosten, Lester; Lau, George
Abstract : ClearVisc was significantly noninferior to Viscoat in the mean percentage of ECD loss from baseline to 3 months and proportion of patients with postoperative IOP ≥30 mm Hg at any follow-up. Abstract : Purpose: To evaluate the safety and effectiveness of a new dispersive ophthalmic viscosurgical device (OVD) (ClearVisc) compared with an approved dispersive OVD (Viscoat) when used in cataract surgery. Setting: 16 clinics in the United States. Design: Prospective multicenter controlled randomized 1:1 (ClearVisc:Viscoat; stratified by site, age group, and cataract severity). Patients and examiners masked. Methods: Patients aged 45 years or older with age-related noncomplicated cataract considered amenable to treatment with standard phacoemulsification cataract extraction and intraocular lens (IOL) implantation were included. Patients were randomized to receive either ClearVisc or Viscoat using standard techniques. 5 postoperative visits occurred at 6 hours, 24 hours, 7 days, 1 month, and 3 months. The primary effectiveness outcome was the change in endothelial cell density (ECD) from baseline to 3 months. The primary safety end point was the proportion of patients who experienced at least 1 intraocular pressure (IOP) measurement ≥30 mm Hg at any follow-up visit. Noninferiority was tested. Inflammation and adverse events were evaluated. Results: 372 patients were randomized: 184 patients in the ClearVisc group and 188 patients in the Viscoat group. ClearVisc was noninferior to Viscoat in mean percentage of ECD loss from baseline to 3 months (8.4% and 6.8%, respectively). ClearVisc was significantly noninferior to Viscoat in the proportion of patients with postoperative IOP ≥30 mm Hg at any follow-up visit (17.4% and 20.3%, respectively, P = .0002). Conclusions: ClearVisc dispersive OVD provides surgeons with a new option in the continuum of approved dispersive OVDs with beneficial properties as a surgical aid in cataract extraction and IOL implantation.